The Trading Response of Individual Investors to Local Bankruptcies - Christine Laudenbach; Benjamin Loos; Jenny Pirschel; Johannes Wohlfart (Center for Economic Studies and ifo Institute (CESifo), 2020)
We use data from a German online brokerage and a survey to show that retail investors sharply reduce risk-taking in response to nearby firm bankruptcies, which are not predictive of returns. The effects on trading are spatially highly concentrated, immediate and not persistent. They seem to operate through more pessimistic expected returns and increased risk aversion and do not reflect wealth effects or changes in background risks. Investors learn about bankruptcies through immediate coverage in local newspapers. Our findings suggest that non-informative local experiences that make downside risks of stock investment more salient contribute to idiosyncratic short-term fluctuations in trading.
Keywords: D14; G11; 330; individual investors; risk-taking; trading; experiences